Harnessing AEM electrolyzer-level performance through strategically designing the electronic structure of electrocatalysts, enabling dynamic functional switching - Kumar, Sonu; Verma, Tushar Singh; Selvaraj, Kaliaperumal (ACS Catalysis, 2025)
The anion exchange membrane water electrolyzer (AEMWE) is a promising technology for cost-effective hydrogen production. To promote its development and adoption, targeted efforts are focused on finding non-platinum group metal (non-PGM) electrocatalysts that efficiently facilitate the hydrogen evolution reaction (HER) and the oxygen evolution reaction (OER). Nickel sulfides (NiS) are effective OER catalysts; however, they suffer due to leaching-related instability at electrolyzer stack operational conditions. We introduce a rational non-PGM design that enhances stability during the OER while excelling at the HER, showcasing molecular-level insights for a scalable AEMWE zero-gap stack device. NiS coating is applied to the Al-metal-organic framework supported by 3D porous nickel foam (NSMA), leading to charge localization at the interface, which helps in OER by requiring only 322 millivolts at 100 mA cm-2. The main innovation in the NSMA design is a controlled electroreduction process that converts the Millerite phase into Ni3S2, a catalyst (rNSMA). This transformation leads to charge delocalization at the surface and a low overpotential of -80 mV at -100 mA cm-2 for the HER. In a full cell, this catalyst duo requires an overpotential of 1.49 V, outperforming the commercial Pt/Ru catalyst pair at 1.58 V. In a scaled-up 12.96 cm2 AEM electrolyzer single-cell stack, current density rose from 398 to 1062 mA/cm2, maintained for over 100 h at high temperatures, achieving 99% Faradaic efficiency and 100% hydrogen purity. The AEM electrolyzer cell shows a good energy efficiency of 45.50 kWh/kg and a cell efficiency of 86.59%. Detailed studies, including DFT analyses, revealed that electronic structure modification enhances charge delocalization, driving its impressive performance on an industrially significant scale.
Keywords: anion exchangemembrane water electrolyzer (AEMWE); charge transfer; density functional theory(DFT); HER; nickel sulfide; OER

Highly active and durable MNS bifunctional electrocatalysts for enhanced anion exchange membrane water electrolysis - Singh, Kailash; Yadav, Himanshu; Samdani, Kunda; Selvaraj, Kaliaperumal (Electrochimica Acta, 2025)
The development of non-platinum group metal (non-PGM) electrocatalysts with performance comparable to their noble metal counterparts remains a significant challenge for overall water splitting. In this study, we demonstrate the performance of an Anion Exchange Membrane (AEM) water electrolyzer using a bifunctional, non-PGM electrocatalyst: reduced graphene oxide (rGO)-encapsulated MoS2/Ni3S2 (MNS) grown on a nickel foam (NF) substrate. The rGO/MoS2/Ni3S2 (rGO-MNS) electrode was synthesized via a facile, single-step hydrothermal method. For the hydrogen evolution reaction (HER), the rGO-MNS electrode exhibited a low overpotential of 94 mV at a current density of 100 mA cm-2, maintaining excellent stability over 50 h with a minimal degradation rate of 120 mu V h-1. In the case of the oxygen evolution reaction (OER), an overpotential of 410 mV was required to reach the same current density, with a similarly robust durability and a degradation rate of only 360 mu V h-1. When employed as symmetric electrodes for overall water electrolysis, the rGO-MNS system achieved a current density of 10 mA cm-2 at a cell voltage of 1.51 V, outperforming the benchmark Pt/C & Vert;Ru/C catalyst pair, which required 1.58 V to reach the same performance. The enhanced electrocatalytic activity and durability are attributed to the conductive rGO encapsulation, which facilitates charge transfer and mitigates surface oxidation of the catalyst. These results present a promising strategy for designing cost-effective, durable, and highperformance non-PGM electrodes for AEM water electrolysis.
Keywords: Anion Exchange Membrane Water Electrolysis; Bifunctional Electrocatalyst; hydrogen evolution reaction; Oxygen Evolution Reaction; rGO-MNS